Irregular terrains in risk area in the municipality of São José dos Campos, São Paulo, Brazil - Gomes, Maria de Fátima Moura; Valerio Filho, Mario; Mendes, Rodolfo Moreda; Maciel, Lidiane Maria (Risco - Journal of Architecture and Urbanism, 2021)
São José dos Campos, in the São Paulo, has numerous irregular areas in socio-environmental vulnerability, especially in the environmental preservation area and the “Topo de Morro” Area. The objective is to discuss the issue of risk in the city, as a case study we take the neighborhood of Santa Helena, as a hypothesis it is considered that housingpublic policies have caused the impoverished population to occupy peripheral areas without an urban structure. The methodology is descriptive and as results and conclusions it is observed that the municipal actions to mitigate the risks andregularize the neighborhoods are still insufficient.